It's solvable...I got an integer answer. Not really that hard (then again, I have a bachelor's in math).Originally posted by: BigPoppa
First one:
Multiply 1/x by (x-1)/(x-1) and 1/(x-1) by x/x. Easy to solve from there.
Second one:
Not solvable? I'm getting 1 = 5/3.
Is it just -4?Originally posted by: GrouchyLadybug
It's solvable...I got an integer answer. Not really that hard (then again, I have a bachelor's in math).Originally posted by: BigPoppa
First one:
Multiply 1/x by (x-1)/(x-1) and 1/(x-1) by x/x. Easy to solve from there.
Second one:
Not solvable? I'm getting 1 = 5/3.
That gives you a divide by 0 error on the right side of the equation.Originally posted by: DXM
I got y = +4 for the second one.
Very true. I also got y=-4.Originally posted by: minendo
That gives you a divide by 0 error on the right side of the equation.Originally posted by: DXM
I got y = +4 for the second one.
Originally posted by: waffel
I can't get the second one, I don't think it has a solution
y/(y-4) - 5/3 = 4/(y-4)
(y-4)/(y-4) = 5/3
1 = 5/3?
That doesn't work, if you plug that back in you getOriginally posted by: GrouchyLadybug
Very true. I also got y=-4.Originally posted by: minendo
That gives you a divide by 0 error on the right side of the equation.Originally posted by: DXM
I got y = +4 for the second one.
You're right minendo. Funny thing is, I just worked out the problem twice and got +4 twice. So I either need to be sent back to Algebra I or I'm missing a negative sign somewhere.Originally posted by: minendo
That gives you a divide by 0 error on the right side of the equation.Originally posted by: DXM
I got y = +4 for the second one.
y/(y-4) - 5/3 = 4/(y-4)Originally posted by: pray4mojo
y = -6Originally posted by: waffel
I can't get the second one, I don't think it has a solution
y/(y-4) - 5/3 = 4/(y-4)
(y-4)/(y-4) = 5/3
1 = 5/3?
I don't know how you got from y/(y-4) - 5/3 = 4/(y-4) to (y-4)/(y-4) = 5/3.
Okay, my husband the math teacher agrees with you.Originally posted by: waffel
I can't get the second one, I don't think it has a solution
y/(y-4) - 5/3 = 4/(y-4)
(y-4)/(y-4) = 5/3
1 = 5/3?
Yep, the equation has no solution.Originally posted by: waffel
y/(y-4) - 5/3 = 4/(y-4)Originally posted by: pray4mojo
y = -6Originally posted by: waffel
I can't get the second one, I don't think it has a solution
y/(y-4) - 5/3 = 4/(y-4)
(y-4)/(y-4) = 5/3
1 = 5/3?
I don't know how you got from y/(y-4) - 5/3 = 4/(y-4) to (y-4)/(y-4) = 5/3.
add 5/3 to both sides, subtract 4/(y-4) from both sides
y/(y-4) - 4/(y-4) = 5/3
combine terms
(y-4)/(y-4) = 5/3